The Practicality of Popular Ethnobotany Scientific Books on Mangrove Plants Genus Avicennia, Tabanio Village - Ayatul Fajrin; Dharmono Dharmono; Muhammad Zaini (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Learning using popular scientific books based on the local potential of an area is one solution that can be used to overcome problems that often arise such as a lack of student reading interest due to boring teaching materials and learning media in Ethnobotany courses, especially in some ethnobotany studies that require students to interact directly with the community. This development research aims to describe the practicality of a popular scientific book prototype entitled " Etnobotani Tumbuhan Mangrove Genus Avicennia Desa Tabanio". The research method used is the development model by Plomp and Nieveen which is limited to the formative evaluation phase based on the Tessmer model. The results showed that the results of the feasibility test for popular scientific books got an average score of 88.9% with very good criteria and the results of student responses to popular scientific books got an average of 91.56% with criterion very agree This shows that the popular scientific book entitled "Ethnobotany of Mangrove Plants Genus Avicennia Desa Tabanio" is very practical to be used as an enrichment material in ethnobotany learning.Abstrak Pembelajaran dengan menggunakan buku ilmiah populer berdasarkan potensi lokal yang dimiliki sebuah daerah merupakan salah satu solusi yang dapat digunakan untuk mengatasi masalah yang sering muncul seperti kurangnya minat membaca mahasiswa karena bahan ajar dan media pembelajaran yang membosankan pada mata kuliah Etnobotani khususnya pada beberapa kajian etnobotani yang mengharuskan mahasiswa untuk berinteraksi langsung dengan masyarakat. Penelitian pengembangan ini bertujuan untuk mendeskripsikan kepraktisan prototipe buku ilmiah populer yang berjudul “Etnobotani Tumbuhan Mangrove Genus Avicennia Desa Tabanio” Metode penelitian yang digunakan ialah model pengembangan oleh Plomp dan Nieveen yang dibatasi sampai pada fase evaluasi formatif berdasarkan model Tessmer. Hasil penelitian menunjukan hasil uji keterlaksanaan buku ilmiah populer mendapatkan nilai rata-rata 88.9% dengan kriteria sangat baik dan hasil respond mahasiswa terhadap buku ilmiah populer mendapatkan rata-rata 91,56% dengan kriteris sangat setuju. Hal tersebut menunjukan bahwa buku ilmiah populer dengan judul “Etnobotani Tumbuhan Mangrove Genus Avicennia Desa Tabanio” sangat praktis digunakan sebagai bahan pengayaan dalam pembelajaran etnobotani.